3D Printed Composite Scaffolds Incorporating Ruthenium Complex–Loaded Liposomes as a Delivery System to Prevent the Proliferation of MG‐63 Cells. Issue 11 (10th July 2019) - Ye, Lijuan; Wang, Jingguang; Liao, Cancheng; Li, Shuqi; Fang, Yuqi; Yang, Zhuohong; Hu, Yang; Guo, Bohong
Abstract: Owing to the propensity of osteosarcoma to recur and metastasize, the administration of a topical treatment to enhance the therapeutic effect of conventional therapy is necessary. To develop a locally released drug delivery system (DDS) to inhibit the growth and recurrence of osteosarcoma, hydrophobically modified silica nanoparticles (m‐SiO2 )/poly(ε‐caprolactone) (PCL) porous scaffolds are fabricated by 3D printing emulsion inks. Ruthenium‐loaded PEGylated liposomes (RL) are then incorporated into the scaffolds to obtain the Ruthenium‐loaded PEGylated liposome scaffold (RLS) composite. The emulsion inks and the density, porosity, morphology, and mechanical properties of the scaffolds are characterized. The results indicate that the composite DDS has a relatively uniform porous structure with good mechanical properties. Drug is released from RLS in a relatively sustained manner over 48 h, which demonstrates the potential of RLS as a drug carrier. In addition, the MG‐63 cell viability and apoptosis rate are evaluated by MTT assays. The cell experiments reveal that RLS triggers mitochondrial dysfunction resulting in MG‐63 cell apoptosis. All the results indicate that RLS provides a promising approach for improving the treatment of osteosarcoma. Abstract : To develop a locally released drug delivery system to inhibit the growth and recurrence of osteosarcoma, hydrophobically modified silica nanoparticles (m‐SiO2 )/poly(ε‐caprolactone) (PCL) porous scaffolds are fabricated by 3D printing emulsion inks. Ruthenium‐loaded PEGylated liposomes are then incorporated into the scaffolds to obtain the Ruthenium‐loaded PEGylated liposome scaffold (RLS) composite.